2015
DOI: 10.1007/s40502-015-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of liquid culture medium and ex vitro rooting for micropropagation of Acacia nilotica (L.) Del. ssp. cupressiformis

Abstract: A micro-propagation method using liquid culture medium has been developed for Acacia nilotica ssp. cupressiformis. Nodal segments obtained from mature tree (15-20 years old) was used as explants for bud breaking and multiple shoot induction. MS liquid medium with 2.0 mg l -1 of 6-benzylaminopurine (BAP) was the best for shoot bud induction. Further shoots multiplication was achieved by subculturing of in vitro produced shoot clumps (2-3 shoots) in liquid medium supplemented with various concentrations of BAP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The multiplication of shoots in liquid media has several advantages, such as fast rate of multiplication, lack of impurities from agar, dilution of exudates from the explants, and uniform dispersal and better availability of nutrients and growth regulators (Lilia et al, 2002;Ascough and Fennell, 2004;Kalpana et al, 2009;Shekhawat et al, 2014). The liquid medium has been used successfully in various plants systems, especially for micropropagation of tree species (Dandin and Murthy, 2012;Rathore et al, 2014Rathore et al, , 2015. Morphological deformity and deterioration of cultures were not observed in this study; therefore liquid media system could be used in continuous multiplication of shoots of M. citrifolia.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…The multiplication of shoots in liquid media has several advantages, such as fast rate of multiplication, lack of impurities from agar, dilution of exudates from the explants, and uniform dispersal and better availability of nutrients and growth regulators (Lilia et al, 2002;Ascough and Fennell, 2004;Kalpana et al, 2009;Shekhawat et al, 2014). The liquid medium has been used successfully in various plants systems, especially for micropropagation of tree species (Dandin and Murthy, 2012;Rathore et al, 2014Rathore et al, , 2015. Morphological deformity and deterioration of cultures were not observed in this study; therefore liquid media system could be used in continuous multiplication of shoots of M. citrifolia.…”
Section: Tablementioning
confidence: 99%
“…Subramani et al (2007) observed rhizogenic calli on MS media with the combination of cytokinin and auxin. Use of IBA as better growth regulator for in vitro root induction has been reported by various researchers in many plant species (Ganesh and Sreenath, 2000;Kavitha et al, 2009;Saha et al, 2010;Nair et al, 2012;Rathore et al, 2014Rathore et al, , 2015Ozel et al, 2015). The rooting Note: Mean separation was analyzed by ANOVA using SPSS software (var.…”
Section: In Vitro Rooting Of Shootsmentioning
confidence: 99%
See 1 more Smart Citation